APLIKASI IRIGASI TETES “RO DRIP” PADA LAHAN KERING - -, Yusriadi; -, Harsani (Lembaga Penelitian dan Pengabdian pada Masyarakat Universitas Bosowa, 2020)
Drip irrigation application is an irrigation system using a drip hose, which aims to make water use effective. Drip irrigation is not a new technology, but has long been developed especially on agricultural land that lacks water resources. Insufficient water sources on agricultural land, so farmers must rely on pumping systems from the nearest water source. With a direct pumping system will increase production costs. For one-time irrigation directly using pumping, farmers need at least 12 liters of fuel oil / day / ha. In other words, farmers must incur additional costs for irrigation purposes. Whereas for the time brackets of horticultural plants, it takes approximately three months for the plants to produce. If farmers have to irrigate land 3 to 4 times per month, farmers need 36 liters of fuel oil per month / ha. Assuming the price of premium fuel oil is Rp 6,650 / liter, then the farmer must at least pay an additional fee of Rp. 239,400 / month / ha. Therefore, the application of